Comparative study of proficiency improvement in ArtiSential® according to conventional laparoscopic surgery experiences. - Rho, Seoung Yoon; Choi, Munseok; Kim, Sung Hyun; Hong, Seung Soo; Kim, Hyoung-il; Lee, Yoo-Young; Kim Poh, Brian Goh; Nagakawa, Yuichi; Tanabe, Minoru; Asano, Daisuke; Kang, Chang Moo (Minimally Invasive Therapy & Allied Technologies, 2025)
Background: This pilot study investigates the adaptability of the articulating instrument (ArtiSential) among surgeons with different levels of experience in conventional laparoscopic surgery. Methods: From June to November 2023, 18 laparoscopic surgeons participated in peg transfer and suture training using ArtiSential instruments. Participants were categorized into novice, intermediate, and expert groups. Peg transfer was repeated three times, comparing dominant and non-dominant hand. Suture training was conducted at four directional positions (1, 12, 3, and 5 o'clock) and analyzed across three trials. Results: In terms of peg transfer timing analysis, there are significant differences between the three groups in the first (p < 0.001) and second trials (p = 0.011). However, in the third trial, the gap between the three groups decreased. In all three groups, the suture times at 3 o'clock and 5 o'clock were consistently lower compared to the 1 o'clock and 12 o'clock directions. As the trials progressed, the time decreased for suturing in all directions. Among them, the novice group had reduced suture times at 3 o'clock and 5 o'clock direction. Conclusions: The ArtiSential instrument is adaptable even for novices. Its articulating features facilitate suturing in traditionally difficult directions (3 o'clock and 5 o'clock) for right-handed users.